2010
DOI: 10.1007/s00774-010-0234-8
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of soy isoflavone and fish oil on ovariectomy-induced bone loss in mice

Abstract: Both soy isoflavone and n-3 polyunsaturated fatty acids are known to reduce the levels of bone-resorbing cytokines; however, the synergistic effects of these food ingredients have not been examined yet. This study was performed to elucidate the effect of concomitant intake of soy isoflavone and fish oil on bone mass in ovariectomized mice. Eight-week-old ddY female mice were subjected to ovariectomy (OVX) or sham surgery, and then fed an AIN-93G with safflower oil (So) as a control lipid source, isoflavone-sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 51 publications
0
9
1
Order By: Relevance
“…Supplementation with fish oil and/or genistein conserves the bone and prevents MTX chemotherapy-induced bone loss by suppressing osteoclastogenesis and stimulating osteogenesis while concurrently inhibiting adipogenesis in bone marrow. No additive or synergistic protection was observed when fish oil and genistein were administered in combination in this current study, although two previous studies have shown that genistein and fish oil additively induced parameters of bone structure and increased bone mass synergistically in an ovariectomy-induced bone loss model [78], [79]. Despite this, the promising effects of fish oil and genistein, shown in the current study, suggest that their therapeutic potential in preventing MTX chemotherapy-induced bone loss warrants further evaluation.…”
Section: Discussioncontrasting
confidence: 71%
“…Supplementation with fish oil and/or genistein conserves the bone and prevents MTX chemotherapy-induced bone loss by suppressing osteoclastogenesis and stimulating osteogenesis while concurrently inhibiting adipogenesis in bone marrow. No additive or synergistic protection was observed when fish oil and genistein were administered in combination in this current study, although two previous studies have shown that genistein and fish oil additively induced parameters of bone structure and increased bone mass synergistically in an ovariectomy-induced bone loss model [78], [79]. Despite this, the promising effects of fish oil and genistein, shown in the current study, suggest that their therapeutic potential in preventing MTX chemotherapy-induced bone loss warrants further evaluation.…”
Section: Discussioncontrasting
confidence: 71%
“…(151,152) Decrease inflammation (150) Promote osteoblastogenesis (151,152) Increase inflammation (150) Decrease osteoblastogenesis (151,152) Osteoclasts Promote osteoclastogenesis? (153,154) Increase BMD (155)(156)(157) Inhibit bone resorption and osteoclastogenesis (158,159) Promote osteoclastogenesis? (159)(160)(161) BMD, bone mineral density; PUFAs, polyunsaturated fatty acids; SFAs, saturated fatty acids.…”
Section: Emerging Dietary Issues: Polyunsaturated Fatty Acids and Polmentioning
confidence: 99%
“…In animals, dietary supplementation with n-3 PUFA-rich oils, including fish oil, has been linked to improved maintenance of bone mass postovariectomy (8)(9)(10). In addition, endogenously produced n-3 PUFAs have been revealed to protect against ovariectomy-induced bone loss in fat-1 transgenic mice (11,12).…”
Section: Introductionmentioning
confidence: 98%